Adoption of Sustainable Production Process to Bring Forth Value Addition in the Indian Seafood Products - Puthusseril, Viju; Kumar, Jyothi (Journal of Ecohumanism, 2024)
Value addition refers to enhancements made to a product before it reaches customers, altering its nature to command a higher price. Currently, the fishing sector grapples with economic challenges like market fluctuations, Illegal, Unreported, and Unregulated (IUU) fishing, and global access constraints. One issue is that fish processors often prioritize maximizing the value of primary products, neglecting potential gains from by-products. The Indian seafood industry faces sustainability, value addition, and market access challenges, particularly in utilizing by-products effectively due to insufficient investment in enhancing their value. This study examines the fish value chain involving fishermen, cooperatives, wholesalers, retailers, and processors. Qualitative analysis sheds light on industry practices, regulatory dynamics, and socio-cultural influences, enhancing resource management considerations. Integration of qualitative insights with quantitative data promises advancements in fishery science and management. Key findings highlight opportunities in value-added exports, seasonal variability impacts, and the critical role of food safety training. Wholesalers in India enjoy higher profit margins, while retailers could enhance profitability through cost reduction and increased sales. Retailers in India could enhance profitability through cost reduction and increased sales. Sustainable practices and efficient supply chains are imperative for the long-term sustainability of India’s seafood sector.